ON THE SIMULATION OF MODES ОF ELECTRIC POWER SYSTEMS WITH FACTS - E. D. Halilov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Power flow control is an important task of development of electric power systems. It is necessary to reduce the power loss, improve the reliability and quality of power supply and increase the power transmission. Currently, on the basis of modern power electronics effective FАСТS devices for flexible control of power system operation modes have been developed. FАСТS devices are able to simultaneously influence the voltage, the reactance, the angle between the voltages. As it is known, the calculations of the established modes of electric systems are the most frequently performed tasks at all the territorial and time levels of control and planning operations. These calculations are significant by themselves, being also an integral part of software systems of calculation of losses of power and energy in electrical networks, calculation of optimal modes and also sustainability. The need for multiple mode calculation imposes high requirements to the methods of calculation of the established modes in real time in terms of performance and reliability of the results of the solution being obtained under operating conditions of electric power systems. In traditional calculations of the established modes of electrical networks, shunt reactors, current-limiting reactors, capacitor banks, longitudinal compensation devices were accounted in the simulation as passive elements. In regard with the introduction of FACTS devices in power systems, there is an arising need to develop appropriate algorithms and implement them in the form of software for analyzing and controlling the established modes of power systems. The methodology and software for calculation of the established modes of electric networks with consideration of FACTS devices have been developed. The software makes it possible to obtain practically acceptable solutions in three outer iterations. Based on the results of numerical simulation of modes of the power system of the “Azerenergy” JSC it was determined that the application of FACTS devices can significantly increase the transmission line active power, improve voltage levels and reduce losses of active power. The dependences of flows and power losses on the control parameter of FACTS devices have been derived.